Aerospace series. Titanium alloy TI-P64003. Cold worked and stress relieved. Seamless tube for pressure systems. 4 mm ≤ D ≤ 51 mm. 690 MPa ≤ Rm ≤ 1 030 MPa. (29th February 2012) - British Standards Institution,
No abstract available